Inflammatory Bowel Diseases: When Natural Friends Turn into Enemies—The Importance of CpG Motifs of Bacterial DNA in Intestinal Homeostasis and Chronic Intestinal Inflammation - Florian Obermeier; Claudia Hofmann; Werner Falk (International Journal of Inflammation)
From numerous studies during the last years it became evident that bacteria and bacterial constituents play a decisive role both in the maintenance of intestinal immune homeostasis as well as in the development and perpetuation of chronic intestinal inflammation. In this review we focus on the role of bacterial DNA which is a potent immunomodulatory component of the bacterial flora. Bacterial DNA has been shown to be protective against experimental colitis. In contrast bacterial DNA essentially contributes to the perpetuation of an already established chronic intestinal inflammation in a Toll-like receptor (TLR)9-dependent manner. This dichotomic action may be explained by a different activation status of essential regulators of TLR signaling like Glycogen synthase kinase 3-𝛽 (GSK3-𝛽) depending on the pre-activation status of the intestinal immune system. In this review we suggest that regulators of TLR signaling may be interesting therapeutic targets in IBD aiming at the restoration of intestinal immune homeostasis.